2007
DOI: 10.1080/09513590701557523
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in endometrium of hemodialyzed women of reproductive age

Abstract: Abnormal endometrial changes are often noted in uremic women of reproductive age undergoing hemodialysis. Endometrial biopsy should be carried out as a safe and convenient procedure for the detection of pathological changes in uremic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Fourteen studies (18,23,24,27,29,33,(35)(36)(37)(38)(39)(40)(41)(42)(43) reported hormone therapy/contraceptive use, although numerous (15,34,(44)(45)(46)(47) considered hormone therapy as exclusion criteria. Eight dialysis-specific articles (24,(39)(40)(41)(42)(43)48) reporting on 585 individuals reported low use of hormone replacement therapy (n5363), oral contraceptives (n56), and intrauterine devices (n52) among study participants.…”
Section: Hormonal Therapy Usementioning
confidence: 99%
“…Fourteen studies (18,23,24,27,29,33,(35)(36)(37)(38)(39)(40)(41)(42)(43) reported hormone therapy/contraceptive use, although numerous (15,34,(44)(45)(46)(47) considered hormone therapy as exclusion criteria. Eight dialysis-specific articles (24,(39)(40)(41)(42)(43)48) reporting on 585 individuals reported low use of hormone replacement therapy (n5363), oral contraceptives (n56), and intrauterine devices (n52) among study participants.…”
Section: Hormonal Therapy Usementioning
confidence: 99%
“…In addition, endometrial atrophy due to changes in the hypothalamic-pituitary-gonadal axis is common in predialyitic and hemodialysis female patients cause a disrupted ovulation process. Even if the menstrual cycle is regular, implantation impairment may occur due to changes in the pulsatility of hypothalamic-pituitary-gonadal hormones [6,7].…”
Section: Introductionmentioning
confidence: 99%